Strategi Manajemen Komunikasi Dalam Menghadapi Tantangan Multikulturlarisme Dalam Konteks Islam - Dio Jidan Ramadhan; Nanda Saputra; Agung Setiawan; Ismail Mubarok (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Communication management strategies in facing the challenges of multiculturalism in the Islamic context have become the focus of research in various Islamic educational and da'wah institutions in Indonesia. The research highlights various communication management strategies used by Islamic education foundations, Islamic da'wah centers, and individuals such as Ust. Felix Siauw. These strategies include mass communication management, internal communication management, external communication management, and Islamic communication strategies in increasing religious understanding by converts. This study also emphasizes the importance of Islamic messages conveyed in Islamic communication, which includes Islamic teachings, creed, sharia, and morals. In the context of Islamic education, da'wah communication strategies are also used to instill moral values in orphanages. The results of this study provide valuable insights in developing effective communication strategies in the context of multiculturalism and in Islam in Indonesia.